Early repolarization as a distractor in acute coronary syndrome: a case report - More-Terán, Juan Carlos (2025)
Electrocardiographic findings in ST-segment elevation acute myocardial infarction do not always evolve in a typical manner, with concomitant changes such as early repolarization that can cause diagnostic confusion. We present the case of a patient with typical chest pain and an atypical electrocardiogram, in which the presence of early repolarization in the inferior leads caused subtle changes in the precordial leads to be overlooked, leading to an error in the initial diagnosis but not in the treatment.